Evaluation of in vitro and in vivo anti atherogenic activities of selected extracts from Pleurotus pulmonarius (Fr.) Quél in comparison between conventional and ultrasound-assisted extraction techniques / Nur Amalina Amirullah - Nur Amalina , Amirullah (2021)
Cardiovascular diseases are the main cause of death worldwide. They cause about 25% of deaths in public hospitals and hence the most common cause of deaths there. On the average, Malaysians develop heart problems at a younger age compared to nationalities in other Southeast Asian countries. Atherosclerosis is the major contributing pathophysiology underlying cardiovascular diseases. It is defined as the thickening of the atherosclerotic walls due to endothelial injury. Various factors contribute to atherogenesis including hypertension, oxidative stress, hyperlipidaemia, and chronic inflammation. Drug usage for the treatment of various cardiovascular conditions have undesirable side effects such as muscle pain, physical weakness, tiredness, and digestive problems. Thus, complementary therapeutics using safer natural compounds are sought. Pleurotus pulmonarius (Fr.) Quél, also known as the Grey Oyster mushroom, is widely used in cuisines. Aside from its enjoyable texture and flavour, the mushroom has also been proven to possess multiple health properties. Thus, this study aimed to evaluate the anti-atherogenic potential of P. pulmonarius both in in vitro and in vivo models. The P. pulmonarius extracts were prepared using conventional (hot water and Soxhlet) and ultrasonic techniques. The activities of these extracts were evaluated using several antioxidant assays, and extracts with the best activities were chosen for further analyses. Two extracts from the ultrasound extraction: E2 (50 min, 140 W) and E3 (30 min, 140 W), and the Soxhlet extract were chosen for characterisation and in vitro cell work using murine macrophage cells, RAW 264.7. The E2 extract exhibited remarkable anti- inflammatory activities as it was able to significantly suppress nitric oxide production at a low concentration of 6.25 μg/mL. The E2 extract at 100 μg/mL also inhibited NF-κB activation in LPS-stimulated RAW 264.7 cells. Due to its superior activities, the E2 extract was chosen for the in vivo experiments using Wistar-Kyoto rats. In this study, the animal model was used to determine the toxicity of the P. pulmonarius E2 extract, as well as its preventive and protective effects. The E2 extract was proven to be non-toxic to the Wistar-Kyoto rats, as it had a lethal dose of over 2000 mg/kg body weight (b. w.). This showed that the P. pulmonarius extract was safe to be consumed. In the treatment experiment, rats were concurrently treated with the E2 extract as well as a high fat diet. Data from the treatment experiment showed that the E2 extract had hypolipidaemic, anti-inflammatory, and anti-oxidative effects in rats. Histological analyses showed that the E2 extract preserved hepatocyte architecture in rats fed with high fat diet. In the preventive experiment, the rats were pre-treated with the E2 extract, and subsequently treated with high fat diet. The preventive study aimed to investigate the potential of the extract to confer protective effects in the rats even when they had stopped receiving the E2 treatment. Data from the preventive experiment proved that the E2 extract had hypolipidaemic, anti-inflammatory, hypoglycaemic, and anti-oxidative effects. The results from the in vitro and in vivo experiments demonstrated the anti-atherogenic activities of the E2 extract. Thus, the P. pulmonarius extract has the potential to alleviate and prevent atherosclerotic conditions.